Sagittal balance of the spine : from normal to pathology : a key for treatment strategy - Roussouly, Pierre; Pinheiro-Franco, João Luiz; Labelle, Hubert; Gehrchen, Martin (Thieme, 2019)
Unique resource from internationally renowned experts details the key role of sagittal spine balance Through evolution, human verticality became associated with a wide range of normal pelvic shapes and associated pelvic incidence angles (PIs). While all types of sagittal alignment generally provide adequate support to young adults, age, stress, and related degeneration can progressively lead to sagittal imbalance and contribute to various spinal pathologies. Sagittal Balance of the Spine by Pierre Roussouly, João Luiz Pinheiro-Franco, Hubert Labelle, Martin Gehrchen, and a cadre of esteemed in